2022-LBA-1282-ESGO Identifying women with early-stage cervical cancer at low risk of lymph node metastases, in a large international cohort – A logistic regression analysis, without sharing privacy-sensitive patient data. (27th October 2022) - Wenzel, Hans; Hardie, Anna Norberg; Bekkers, Ruud; Falconer, Henrik; Høgdall, Claus; Jensen, Pernille; Lemmens, Valery; Martin, Frank; Moncada-Torres, Arturo; Nijman, Hans; van der Aa, Maaike; Schnack, Tine; et al.
Abstract : Introduction: Standard treatment of early-stage cervical cancer is radical hysterectomy with pelvic lymphadenectomy. However, a generic benefit of systematic lymphadenectomy is questionable, as most women will not have metastatic nodes. This study aimed to classify the most important risk factors of lymph node metastases (pN+) and to identify a group of women at low risk of pN+, in a large cohort of Danish, Swedish and Dutch women, using federated learning. Methods: Women diagnosed with cervical cancer between 2005–2020 were identified from nationwide population-based registries: the Danish Gynaecological Cancer Database, Swedish Quality Registry of Gynaecologic Cancer and Netherlands Cancer Registry. Inclusion criteria were: squamous cell carcinoma, adenocarcinoma or adenosquamous carcinoma; FIGO 2009 stage IA2, IB1 and IIA1; treatment with radical hysterectomy and pelvic lymph node assessment. We applied privacy-preserving federated logistic regression to identify risk factors of pN+ ( figure 1 ). Significant factors were used to identify a low-risk group (pN+ &le5%). Results: A total of 3, 606 women were included. The most important risk factors of pN+ were lymphovascular space invasion (LVSI) (odds ratio [OR] 5.16, 95% confidence interval [CI] 4.59–5.79), tumour size 21–40 mm (OR 2.14, 95% CI 1.89–2.43) and depth of invasion &gt10 mm (OR 1.81, 95% CI 1.59–2.08]). Tumours without LVSI, a size ≤20 mm and a depth of invasion ≤10 mm were associated with a low risk of pN+ (2%, 95% CI 2–3%) ( table 1 ). Conclusions: LVSI, tumours size and depth of invasion were the most important risk factors of pN+. Based on that, we identified a group at very low risk of pN+, in whom sentinel lymph node mapping should be considered to replace radical pelvic lymphadenectomy.